Pendidikan Moderasi Beragama Di Pesantren: (Study Kasus Di Pondok Pesantren Harisul Khairaat Kota Tidore Kepulauan) - Sugianto, Hendi; Diva, Farnela (Al-Riwayah : Jurnal Kependidikan, 2023)
Islamic boarding schools, as uniquely Indonesian religious educational institutions, possess their own distinctiveness in nurturing and promoting values of religious moderation. This research aims to uncover the values of religious moderation cultivated at the Harisul Khairaat Islamic Boarding School using a qualitative research approach. Data collection techniques in this study involved observation, in-depth interviews, and documentation. Meanwhile, data analysis was conducted using the model developed by Miles, Huberman, and Saldana, which includes data collection, data condensation, data presentation, and drawing conclusions. The results of this research indicate that the values of moderation developed in this boarding school encompass tawassuth (moderation in religious practice), i'tidal (justice), tasamuh (tolerance), syura (consultation), qudwah (leadership), patriotism, and anti-violence.